Early Intervention With Adrenocorticotropin for Acute Encephalopathy-Associated Epileptic Spasms: Report of Two Cases. (January 2019) - Yonemoto, Kousuke; Ichimiya, Yuko; Sanefuji, Masafumi; Kaku, Noriyuki; Sakata, Ayumi; Baba, Rieko; Yamashita, Fumiya; Akamine, Satoshi; Torio, Michiko; Ishizaki, Yoshito; Maehara, Yoshihiko; Sakai, Yasunari; et al.
Purpose . Acute encephalopathy with biphasic seizures and reduced diffusion (AESD) is a leading cause of childhood-onset encephalopathy in Japan. Children with AESD frequently develop intractable epilepsy, whereas their treatment options remain to be determined. Method . We present 2 unrelated girls, who developed AESD at 25 months (case 1) and 12 months of age (case 2). Both cases underwent intensive cares from the first day of illness, whereas severe neurological impairments were left on discharge. They showed repeated signs of epileptic spasms at 2 months (case 1) and 8 months (case 2) after the onset of AESD. Video-monitoring electroencephalograms (EEG) detected the recurrent attacks accompanying slow-wave bursts and transient suppressions of the precedent epileptiform discharges, as typically observed in epileptic spasms. Results . Intramuscular injection of adrenocorticotropic hormone (ACTH, 0.0125 mg/kg/d) was introduced within 1 month from the onset of epileptic spasms and continued for 2 weeks. The ACTH treatment disrupted the paroxysmal activity in EEG, and it has relieved these patients from epileptic seizures for more than 1 year. Conclusion . This report illustrates the potential efficacy of ACTH for a group of children with epileptic spasms after AESD.